2019
DOI: 10.1088/1674-1056/ab3437
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and desorption phenomena on thermally annealed multi-walled carbon nanotubes by XANES study

Abstract: The multi-walled carbon nanotubes (MWCNTs) studied in this work were synthesized by the catalytic chemical vapor deposition (CCVD) process, and were thermally annealed by the hot filament plasma enhanced (HF PE) method at 550 °C for two hours. The x-ray absorption near edge structure (XANES) technique was used to investigate the adsorption and desorption phenomena of the MWCNTs at normal and grazing incidence angles. The adsorbates were found to have different sensitivities to the thermal annealing. The geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…Let us stress that the heat exchange through the annealed process has been shown to cause changes in the binding energy and the intensity of the adsorbates. Compared to our previous results [10,15], we note that the peaks A′′′, A′′′′ and P are not observed in our present spectra due to their extremely low resolution. Thus, we will focus only on the visible peaks in the following.…”
Section: Xanes Results Of Potassium Adsorbed Swcntscontrasting
confidence: 99%
See 3 more Smart Citations
“…Let us stress that the heat exchange through the annealed process has been shown to cause changes in the binding energy and the intensity of the adsorbates. Compared to our previous results [10,15], we note that the peaks A′′′, A′′′′ and P are not observed in our present spectra due to their extremely low resolution. Thus, we will focus only on the visible peaks in the following.…”
Section: Xanes Results Of Potassium Adsorbed Swcntscontrasting
confidence: 99%
“…The FTIR also showed that the functional groups at the surface of SWCNTs are principally OH − , C=O and C≡C. According to our previous results [10,15], the two dominant peaks near 265.94 eV (A) and 277.54 eV (B) were associated with an unoccupied π * and σ * band, respectively. The features corresponding to C and D respectively at 284,43 eV and 293.05 eV were associated with σ-symmetry while Ex.…”
Section: Xanes Results Of Potassium Adsorbed Swcntsmentioning
confidence: 54%
See 2 more Smart Citations